Effects of explicit cueing and ambiguity on the anticipation and experience of a painful thermal stimulus. - Lincoln M Tracy; Stephen J Gibson; Nellie Georgiou-Karistianis; Melita J Giummarra (PLoS ONE, 2017)
Many factors can influence the way in which we perceive painful events and noxious stimuli, but less is known about how pain perception is altered by explicit knowledge about the impending sensation. This study aimed to investigate the impact of explicit cueing on anxiety, arousal, and pain experience during the anticipation and delivery of noxious thermal heat stimulations. Fifty-two healthy volunteers were randomised to receive explicit instructions about visual cue-stimulus temperature pairings, or no explicit instructions about the cue-stimulus pairs. A pain anxiety task was used to investigate the effects of explicit cueing on anticipatory anxiety, pain experience and electrophysiological responses. Participants who received explicit instructions about the cue-stimulus pairs (i.e., the relationship between the colour of the cue and the temperature of the associated stimuli) reported significantly higher subjective anxiety prior to the delivery of the thermal heat stimuli (p = .025, partial eta squared = .10). There were no effects of explicit cueing on subsequent pain intensity, unpleasantness, or the electrophysiological response to stimulus delivery. The perceived intensity and unpleasantness of the stimuli decreased across the blocks of the paradigm. In both groups anticipating the ambiguous cue elicited the largest change in electrophysiological arousal, indicating that not knowing the impending stimulus temperature led to increased arousal, compared to being certain of receiving a high temperature thermal stimulus (both p < .001). Perceived stimulus intensity varied between ambiguous and non-ambiguous cues, depending on the temperature of the stimulus. Together these findings highlight the impact and importance of explicit cueing and uncertainty in experimental pain studies, and how these factors influence the way healthy individuals perceive and react to noxious and innocuous thermal stimuli.